2020
DOI: 10.1016/j.celrep.2020.107846
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Gene JAZF1 Is Essential for the Homeostatic Control of Ribosome Biogenesis and Function in Metabolic Stress

Abstract: Highlights d JAZF1 localizes in the nucleus in high-glucose and metabolic stress conditions d JAZF1 mediates metabolic stress via endoplasmic reticulum and p53 stress pathways d JAZF1 regulates ribosome biogenesis and aminoacyl-tRNA synthetases d JAZF1 is a direct negative regulator of insulin gene transcription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 135 publications
(131 reference statements)
0
46
0
Order By: Relevance
“…The molecular function of the JAZF1 protein is largely unexplored. It is a transcription factor with three C2H2 zinc fingers, and studies have linked it to glucose production, lipid metabolism, ribosome biogenesis, metabolic disorders and pancreatic cancer (Kobiita et al, 2020; Liao et al, 2019; Nakajima et al, 2004; Zhou et al, 2020). The JAZF1 protein has a homolog in S. cerevisiae called Sfp1 (Figure 6A), an essential transcription factor involved in regulation of ribosomal protein (RP), ribosomal biogenesis(RiBi) and cell cycle genes, responding to nutrients and stress through regulation by TORC1 (Lempiainen et al, 2009; Marion et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular function of the JAZF1 protein is largely unexplored. It is a transcription factor with three C2H2 zinc fingers, and studies have linked it to glucose production, lipid metabolism, ribosome biogenesis, metabolic disorders and pancreatic cancer (Kobiita et al, 2020; Liao et al, 2019; Nakajima et al, 2004; Zhou et al, 2020). The JAZF1 protein has a homolog in S. cerevisiae called Sfp1 (Figure 6A), an essential transcription factor involved in regulation of ribosomal protein (RP), ribosomal biogenesis(RiBi) and cell cycle genes, responding to nutrients and stress through regulation by TORC1 (Lempiainen et al, 2009; Marion et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Kobiita et al conducted a study regarding the role of JAZF1 in the homeostatic control of ribosome biogenesis and function in metabolic stress. They found that SNP rs1635852 located in intron X of JAZF1 is a key factor in pancreatic beta-cell for mediating metabolic stress signals and regulating protein translation in response to increased demand for insulin [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that some T2D gene variants increase T2D risk by altering aaRS expression. Kobiita et al also found reduced JAZF1 expression in islets from two T1D patients when compared to four nondiabetic individuals, as well as in islets from eight-week-old NOD mice, a model of autoimmune diabetes [149]. RNA sequencing by Russell et al of FACS-purified pancreatic β-cells from four T1D patients and thirteen nondiabetic individuals showed no changes in JAZF1 or GARS1 expression and a nonsignificant trend for reduced DARS1 levels in T1D β-cells [130].…”
Section: Regulation Of Aarss Expression By T2d Susceptibility Gene Vamentioning
confidence: 96%
“…Kobiita et al recently demonstrated that the T2D susceptibility gene JAZF1, the expression of which is reduced in pancreatic islets of T2D patients, is a transcriptional activator of several aaRS-encoding genes [149]. Interestingly, Jazf1 deficiency in mouse β-cells resulted in reduced expression of Dars and Gars [149], the latter being the aaRS with highest expression in human pancreas [150]. Moreover, they also showed that Gars levels are reduced by 50% in db/db mouse islets, and Gars and Dars silencing sensitize pancreatic β-cells to ER stress-induced apoptosis.…”
Section: Regulation Of Aarss Expression By T2d Susceptibility Gene Vamentioning
confidence: 99%